DINAMIKA KONFLIK YAMAN, DAMPAK DAN RESOLUSINYA - Asriyana Asriyana; Daryanti Daryanti; Hasaruddin Hasaruddin (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2024)
The civil war in Yemen has resulted in a humanitarian crisis full of complexity. Exacerbated by the intervention of Saudi Arabia and its coalition, Yemen is already in the throes of a humanitarian crisis and faces terrorist violence, water shortages, and rampant corruption. Saudi Arabia's intervention increases the intensity of the conflict and worsens the humanitarian crisis occurring in Yemen, which is characterized by an increase in all aspects of the humanitarian crisis, including widespread violence, population displacement, the impact of the conflict on the economy, the need for humanitarian assistance, obstacles to humanitarian assistance, and security threats for humanitarian aid workers. This study is a combination of descriptive and qualitative research. The purpose of this research is to interpret the current situation, attitudes or views that occur in society, the conflict between two or more situations, the influence of a condition, or other things. The Yemeni conflict creates insecurity due to attacks by weapons of war, limited access, and climate change. However, these various causes actually emerged because of the continuation of the war. Therefore, stopping the war is the main thing that needs to be done to prevent continued threats.